Research on Online RF Index Test Method of Cellular Mobile Communication Base Station - Chen Zhang (Dianxin kexue)
The structures of all types of cellular mobile communication base station equipment and the frequency configuration characteristics were briefly introduced, and the online RF index test method and solution of test failures were discussed. Then the test results and emphasized difficulties in practical work were analyzed and evaluated. Finally, the online RF index test of cellular mobile communication base station equipment in the future was prospected.